2017
DOI: 10.1002/jbio.201600225
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cognitive‐test characterization of reconnectable implantable fiber‐optic neurointerfaces for optogenetic neurostimulation

Abstract: Cognitive tests on representative groups of freely behaving transgenic mice are shown to enable a quantitative characterization of reconnectable implantable fiber-optic neurointerfaces for optogenetic neurostimulation. A systematic analysis of such tests provides a robust quantitative measure for the cognitive effects induced by fiber-optic neurostimulation, validating the performance of fiber-optic neurointerfaces for long-term optogenetic brain stimulations and showing no statistically significant artifacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The longer stretch of the fiber bundle is connected to its shorter counterpart, implanted in the mouse brain, only during the time when the measurements are performed (Figure A). All the time between the optical measurements, a mouse lives with a miniature fiber component implant (Figure B), whose weight is less than 0.3 g. That fiber implantation caused no changes in the mouse temperature, weight or behavior was verified in a special set of tests, as described in detail elsewhere . Such a design of a fiberscope, as the earlier studies with implantable single‐fiber neurointerfaces suggest , should make it possible to extend in vivo neuroimaging studies to a period of few weeks or even few months.…”
Section: Methodsmentioning
confidence: 69%
See 2 more Smart Citations
“…The longer stretch of the fiber bundle is connected to its shorter counterpart, implanted in the mouse brain, only during the time when the measurements are performed (Figure A). All the time between the optical measurements, a mouse lives with a miniature fiber component implant (Figure B), whose weight is less than 0.3 g. That fiber implantation caused no changes in the mouse temperature, weight or behavior was verified in a special set of tests, as described in detail elsewhere . Such a design of a fiberscope, as the earlier studies with implantable single‐fiber neurointerfaces suggest , should make it possible to extend in vivo neuroimaging studies to a period of few weeks or even few months.…”
Section: Methodsmentioning
confidence: 69%
“…In this work, we demonstrate reconnectable bundles consisting of thousands of optical fibers, which enable, as our experiments show, high‐quality image transmission, offering a platform for the creation of implantable fiberscopes for minimally invasive in vivo brain imaging. The concept of reconnectable fiberscopes demonstrated in this work extends the idea of reconnectable implantable single‐fiber optical neurointerfaces to the fiber‐bundle imaging technology. Experiments on various lines of transgenic mice presented below in this paper verify the performance of this fiberscope as a powerful tool for chronic in vivo neuroimaging using genetically encoded calcium indicators, neuronal activity markers as well as axon growth regulators and brain‐specific protein drivers in deep regions of awake brain.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A typical fiber‐to‐fiber separation in the fiber bundle is Λ ≈ 3 μm. The length of the section‐A fiber is chosen long enough to allow transgenic mice studied in experiments to freely move within an area, ≈ 1 × 1‐m 2 area, sufficient for open‐field, rotarod, and elevated‐plus‐maze cognitive tests [32].…”
Section: Fiber‐bundle Microendoscopementioning
confidence: 99%
“…As one unwanted complication, brain tissue microinjuries caused by fiber implantation may lead to microglia infiltration, altering the neural tissue on the edges of the implanted fiber probe. However, recent detailed studies of brain‐tissue alterations caused by fiber implantation [10, 32] have not revealed any significant anomalies in the microglia density near the fiber shaft as compared to the tissues in the distant areas. Our histological studies of tissue integrity are fully consistent with these earlier results.…”
Section: Fiber‐bundle Microendoscopementioning
confidence: 99%